Alkaline‐Earth Metal Ion Turn‐On Circularly Polarized Luminescence and Encrypted Selective Recognition of AMP. Issue 10 (2nd September 2020) - Zhao, Yang; Niu, Dian; Tan, Jiajing; Jiang, Yuqian; Zhu, Huajie; Ouyang, Guanghui; Liu, Minghua
Abstract: Circularly polarized luminescence (CPL) provides fundamental insights into the chiral structural information of luminescent materials at their excited states, thus contributing to the possibility of encrypting both chirality and luminescence information into functional materials for multi‐purpose applications such as smart chiroptical devices and encrypted recognition systems. Here, by coordination of alkali‐earth metal ions with a chiral histidine‐functionalized amphiphile (methyl (E)‐(2‐styrylthiazole‐4‐carbonyl)‐l ‐histidinate, abbreviated as STH), both fluorescence (FL), and CPL signals are encoded into the STH metal complexes. Impressively, the CPL‐active STH/Mg 2+ complex features an encrypted selective recognition ability of adenosine monophosphate (AMP) among the three types of adenosine phosphates (ATP, ADP, and AMP), while FL signals cannot distinguish them. It is found that the trans‐cis photo‐isomerization of styrene moiety in the building block leads to significant switching between different molecular configurations, FL and CPL signals, producing a high‐efficiency ON–OFF FL and CPL switch. Although FL switch shows negligible discrimination for three types of adenosines, the CPL‐ON state can efficiently recognize AMP at physiological concentration range, which highlights its prospect as a smart CPL probe toward chiral bioactive compounds. Abstract : By coordination of alkali‐earth metal ions with a chiral histidine‐functionalized amphiphile (STH), fluorescence and circularly polarized luminescence (CPL) signals are encoded into the STH metal complex. The photo‐isomerization of styryl initiated efficient chiroptical photo‐switching. Impressively, the CPL‐ON state features an encrypted selective recognition ability for adenosine monophosphate (AMP) among several adenosine phosphates, while fluorescence signals cannot distinguish them.